Ceramic three-dimensional glaze and preparation method and application thereof

CN122977703APending Publication Date: 2026-10-27LILING HEXING CERAMICS CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611420130.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2026-07-10
Filing Date
2026-09-14
Publication Date
2026-10-27

AI Technical Summary

Technical Problem

[0003]现有的立体釉料制成的立体釉(如普通熔块凸起釉),凸起高度通常难以稳定,且高温下容易流淌塌陷,边缘模糊;表面为光滑硬质玻璃体,触感冰冷坚硬

Benefits of technology

(1)本发明提供的陶瓷立体釉料,透明基础熔块用于形成连续玻璃基体;锆英砂在高温下分解产生ZrO2和SiO2,诱发体积微膨胀;钛酸铝具有高热膨胀系数,与基体膨胀失配产生压应力,促使釉面局部隆起;氧化铈作为晶须生长促进剂(硅酸铈晶须);短切硅酸镁纤维在高温下部分熔融并引导晶须取向生长,形成骨架支撑凸起;聚甲基丙烯酸甲酯微球在烧制时,维持釉料的稳定,防止氧化铈、短切硅酸镁纤维等沉淀,进而导致的釉面塌陷、不平等缺陷。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122977703A_ABST
    Figure CN122977703A_ABST
Patent Text Reader

Abstract

The application belongs to the technical field of glaze preparation, and particularly relates to a ceramic three-dimensional glaze, a preparation method thereof and application. The ceramic three-dimensional glaze comprises the following components in parts by weight: 60-70 parts of transparent base frit, 8-12 parts of zirconium silicate sand, 5-10 parts of aluminum titanate, 5-10 parts of cerium oxide, 3-7 parts of short-cut magnesium silicate fiber, 3-5 parts of polymethyl methacrylate microspheres, 0.5-0.8 parts of suspending agent and 45-50 parts of water. The ceramic three-dimensional glaze provided by the application has obvious protrusions, a smooth surface and uniform color after firing.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of glaze preparation technology, specifically relating to a three-dimensional ceramic glaze, its preparation method, and its application. Background Technology

[0002] Three-dimensional glazes are functional ceramic glazes that, through special formulas and processes, create distinct textures or a three-dimensional visual effect on the glaze surface after firing. Their core characteristic is that the glaze surface is no longer flat, but rather has tangible physical variations in height (such as granular, striped, or foamy textures), thus simultaneously creating a three-dimensional effect both visually and tactilely.

[0003] Existing three-dimensional glazes (such as ordinary frit raised glazes) often have unstable raised heights and are prone to flowing and collapsing at high temperatures, resulting in blurred edges; the surface is a smooth, hard glass, and feels cold and hard to the touch. Summary of the Invention

[0004] To address the aforementioned problems, this invention provides a three-dimensional ceramic glaze, its preparation method, and its application, thereby resolving at least one aspect of the technical issues described above.

[0005] This invention is achieved through the following technical solution: In a first aspect, the present invention provides a ceramic three-dimensional glaze, comprising the following components in parts by weight: 60-70 parts transparent base frit, 8-12 parts zircon sand, 5-10 parts aluminum titanate, 5-10 parts cerium oxide, 3-7 parts chopped magnesium silicate fiber, 3-5 parts polymethyl methacrylate microspheres, 0.5-0.8 parts suspending agent, 45-50 parts water.

[0006] In some possible implementations, the transparent base frit comprises components with the following mass fractions: 59%~66% SiO2, 10%~15% Al2O3, 3%~6% CaO, 4%~8% MgO, 1%~5% ZnO, 5%~16% flux.

[0007] In some possible implementations, the flux includes B2O3.

[0008] In some possible implementations, the flux also includes alkali metal oxides.

[0009] In some possible implementations, the alkali metal oxide includes at least one of K2O, Na2O, and Li2O.

[0010] In some possible implementations, the zircon sand has a particle size D50 ≤ 1.5 μm.

[0011] In some possible implementations, the particle size D50 of the aluminum titanate is 3 μm to 5 μm.

[0012] In some possible implementations, the cerium oxide has a particle size D50 of 50 nm to 100 nm.

[0013] In some possible implementations, the length of the chopped magnesium silicate fiber is 50 μm to 150 μm.

[0014] In some possible implementations, the aspect ratio of the chopped magnesium silicate fibers is 500 to 1000.

[0015] In some possible implementations, the suspending agent includes carboxymethyl cellulose.

[0016] Secondly, the present invention provides a method for preparing the above-mentioned ceramic three-dimensional glaze, comprising the following steps: After ball milling transparent base frit, zircon sand, aluminum titanate and cerium oxide, short-cut magnesium silicate fiber, polymethyl methacrylate microspheres and suspending agent are added and stirred and mixed. Water is then added and the mixture is aged.

[0017] In some possible implementations, the particle size D90 of the product obtained by the mixed ball milling is <10 μm.

[0018] In some possible implementations, the stirring speed for mixing is 50 rpm to 80 rpm.

[0019] In some possible implementations, the mixing time is 3 to 5 minutes.

[0020] In some possible implementations, the aging time is 24h to 26h.

[0021] Thirdly, the present invention provides an application of the above-mentioned three-dimensional ceramic glaze in ceramic glaze processing.

[0022] The ceramic three-dimensional glaze provided by this invention has at least the following beneficial technical effects compared with the prior art: (1) The ceramic three-dimensional glaze provided by the present invention uses a transparent base frit to form a continuous glass matrix; zircon sand decomposes at high temperature to produce ZrO2 and SiO2, which induces micro-expansion in volume; aluminum titanate has a high coefficient of thermal expansion, which mismatches with the matrix expansion and generates compressive stress, causing local bulging of the glaze surface; cerium oxide is used as a whisker growth promoter (cerium silicate whiskers); short-cut magnesium silicate fibers partially melt at high temperature and guide the whisker orientation growth to form a skeleton to support the protrusions; polymethyl methacrylate microspheres maintain the stability of the glaze during firing and prevent the precipitation of cerium oxide, short-cut magnesium silicate fibers, etc., which would lead to glaze surface collapse and uneven defects.

[0023] (2) The ceramic three-dimensional glaze provided by the present invention has obvious protrusions, smooth surface and uniform color after firing. Attached Figure Description

[0024] To more clearly illustrate the technical solutions in the embodiments of this drawing or the prior art, the drawings used in the description of the embodiments or the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of this drawing. For those skilled in the art, other drawings can be obtained based on the structures shown in these drawings without creative effort.

[0025] Figure 1 This is a firing effect diagram of the three-dimensional glaze of the ceramic three-dimensional glaze provided in Embodiment 1 of the present invention.

[0026] The purpose, features, and advantages of this accompanying drawing will be further explained in conjunction with the embodiments and with reference to the accompanying drawing. Detailed Implementation

[0027] To make the objectives, technical solutions, and advantages of this invention clearer, the invention is described and illustrated below with reference to embodiments. It should be understood that the specific embodiments described herein are merely illustrative and not intended to limit the invention. All other embodiments obtained by those skilled in the art based on the embodiments provided by this invention without inventive effort are within the scope of protection of this invention.

[0028] Obviously, the following description is merely some examples or embodiments of the present invention. Those skilled in the art can apply the present invention to other similar scenarios without any inventive effort. Furthermore, it is understood that although the effort involved in such development may be complex and lengthy, for those skilled in the art related to the content disclosed in this invention, modifications to design, manufacturing, or production based on the technical content disclosed in this invention are merely conventional technical means and should not be construed as insufficient disclosure of the present invention.

[0029] However, there may be instances where unnecessary detailed descriptions are omitted. For example, detailed descriptions of well-known matters or repetitive descriptions of essentially the same structures may be omitted. This is to avoid making the following description unnecessarily lengthy and to facilitate understanding by those skilled in the art. Furthermore, the following description is provided to enable those skilled in the art to fully understand the invention and is not intended to limit the subject matter of the claims.

[0030] Unless otherwise specified, all embodiments and optional embodiments of the present invention can be combined with each other to form new technical solutions, and all technical features and optional technical features of the present invention can be combined with each other to form new technical solutions.

[0031]

Ceramic 3D Glaze

[0032] The ceramic three-dimensional glaze provided in this invention uses a transparent base frit to form a continuous glass matrix; zircon sand decomposes at high temperature to produce ZrO2 and SiO2, inducing micro-expansion; aluminum titanate has a high coefficient of thermal expansion, and its expansion mismatch with the matrix generates compressive stress, causing local bulging of the glaze surface; cerium oxide acts as a whisker growth promoter (cerium silicate whiskers); short-cut magnesium silicate fibers partially melt at high temperature and guide the whisker orientation growth, forming a framework to support the protrusions; polymethyl methacrylate microspheres maintain the stability of the glaze during firing, preventing the precipitation of cerium oxide, short-cut magnesium silicate fibers, etc., which would lead to glaze collapse and unevenness defects. The ceramic three-dimensional glaze provided in this invention has obvious protrusions, a smooth surface, and uniform color after firing.

[0033] In some embodiments, the transparent base frit comprises components with the following mass fractions: 59%~66% SiO2, 10%~15% Al2O3, 3%~6% CaO, 4%~8% MgO, 1%~5% ZnO, 5%~16% flux.

[0034] In this context, SiO2 acts as the glass network forging body, serving as the framework; Al2O3 is used to improve chemical stability and hardness; CaO is used to adjust the coefficient of thermal expansion of the glaze and improve its gloss; MgO is used to reduce the coefficient of thermal expansion and increase durability; ZnO is used to improve the gloss and elasticity of the glaze; and flux is used to reduce the melting temperature and viscosity of the glaze.

[0035] In some embodiments, the flux includes B2O3.

[0036] In some embodiments, the flux also includes alkali metal oxides.

[0037] In some specific embodiments, the alkali metal oxide includes at least one of K2O, Na2O, and Li2O.

[0038] In some embodiments, the particle size D50 of the zircon sand is ≤1.5μm.

[0039] In some embodiments, the particle size D50 of aluminum titanate is 3 μm to 5 μm.

[0040] In some embodiments, the particle size D50 of cerium oxide is 50 nm to 100 nm.

[0041] In some embodiments, the length of the chopped magnesium silicate fiber is 50 μm to 150 μm.

[0042] In some embodiments, the aspect ratio of the chopped magnesium silicate fibers is 500 to 1000.

[0043] In some embodiments, the CAS number of polymethyl methacrylate in the polymethyl methacrylate microspheres is 9010-88-2.

[0044] In some embodiments, the average particle size of the polymethyl methacrylate microspheres is 80 μm to 200 μm.

[0045] In some embodiments, the suspending agent includes carboxymethyl cellulose.

[0046] Preparation methods for three-dimensional ceramic glazes A second aspect of the present invention provides a method for preparing the above-mentioned three-dimensional ceramic glaze, comprising the following steps: S10. After ball milling a mixture of transparent base frit, zircon sand, aluminum titanate and cerium oxide, short-cut magnesium silicate fiber, polymethyl methacrylate microspheres and suspending agent are added and stirred. Water is then added and the mixture is aged.

[0047] The method for preparing ceramic three-dimensional glaze provided in this invention involves first mixing and ball milling transparent base frit, zircon sand, aluminum titanate, and cerium oxide to uniformly refine the particle size; then adding chopped magnesium silicate fibers, polymethyl methacrylate microspheres, and a suspending agent to prevent the structure of the chopped magnesium silicate fibers and polymethyl methacrylate microspheres from being damaged by ball milling; finally, adding water to adjust the glaze viscosity (paste-like consistency); and aging to stabilize and homogenize the glaze slurry, improve its fluidity, and enhance its adhesion.

[0048] In some embodiments, in step S10 above, the particle size D90 of the product obtained by ball milling is <10 μm.

[0049] In some specific embodiments, the mixing method in step S10 above is dry mixing.

[0050] In some embodiments, in step S10 above, the stirring speed for mixing is 50 rpm to 80 rpm.

[0051] In some embodiments, the mixing time in step S10 is 3 min to 5 min.

[0052] In some embodiments, the aging time in step S10 is 24h to 26h.

[0053] The following description, in conjunction with specific embodiments, provides further details.

[0054] For ease of explanation, the following embodiments and comparative examples involve: (1) The particle size of zircon sand is D50≤1.5μm.

[0055] (2) The particle size D50 of aluminum titanate is 3μm~5μm. (3) The particle size D50 of cerium oxide is 50nm~100nm.

[0056] (4) The CAS number of polymethyl methacrylate is 9010-88-2.

[0057] Example 1 Example 1 provides a ceramic three-dimensional glaze, which is composed of the following raw materials in parts by weight: 65 parts transparent base frit, 10 parts zircon sand, 8 parts aluminum titanate, 8 parts cerium oxide, 5 parts chopped magnesium silicate fiber, 4 parts polymethyl methacrylate microspheres, 0.6 parts carboxymethyl cellulose, and 50 parts water.

[0058] The transparent base frit is composed of the following components by mass fraction: 63% SiO2, 12% Al2O3, 5% CaO, 6% MgO, 3% ZnO, 11%B2O3.

[0059] The chopped magnesium silicate fiber has a length of 100 μm and an aspect ratio of 800.

[0060] The average particle size of the polymethyl methacrylate microspheres is 100 μm.

[0061] This embodiment also provides a method for preparing the above-mentioned three-dimensional ceramic glaze, the steps of which are as follows: E10. Transparent base frit, zircon sand, aluminum titanate and cerium oxide are mixed and ball-milled until the product particle size D90 < 10 μm. Short-cut magnesium silicate fiber, polymethyl methacrylate microspheres and suspending agent are added and stirred and mixed (dry mixing). Water is then added and mixed and aged.

[0062] The stirring speed for mixing was 60 rpm and the time was 4 min. The aging time is 24 hours.

[0063] Example 2 Example 2 provides a ceramic three-dimensional glaze, which is composed of the following components in parts by weight: 60 parts transparent base frit, 8 parts zircon sand, 5 parts aluminum titanate, 5 parts cerium oxide, 3 parts chopped magnesium silicate fiber, 3 parts polymethyl methacrylate microspheres, 0.5 parts carboxymethyl cellulose, and 45 parts water.

[0064] The transparent base frit is composed of the following components by mass fraction: 63% SiO2, 12% Al2O3, 5% CaO, 6% MgO, 3% ZnO, 10% B2O3, 1% K2O.

[0065] The chopped magnesium silicate fiber has a length of 50 μm and an aspect ratio of 500.

[0066] The average particle size of the polymethyl methacrylate microspheres is 80 μm.

[0067] This embodiment also provides a method for preparing the above-mentioned three-dimensional ceramic glaze, the steps of which are as follows: E11. Transparent base frit, zircon sand, aluminum titanate and cerium oxide are mixed and ball-milled until the product particle size D90 < 10 μm. Short-cut magnesium silicate fiber, polymethyl methacrylate microspheres and suspending agent are added and stirred and mixed (dry mixing). Water is then added and the mixture is aged.

[0068] The mixing speed was 50 rpm and the mixing time was 5 min. The aging time is 24 hours.

[0069] Example 3 Example 3 provides a ceramic three-dimensional glaze, which is composed of the following components in parts by weight: 70 parts transparent base frit, 12 parts zircon sand, 10 parts aluminum titanate, 10 parts cerium oxide, 7 parts chopped magnesium silicate fiber, 5 parts polymethyl methacrylate microspheres, 0.8 parts carboxymethyl cellulose, and 50 parts water.

[0070] The transparent base frit is composed of the following components by mass fraction: 63% SiO2, 12% Al2O3, 5% CaO, 6% MgO, 3% ZnO, 8%B2O3, 3%Na2O.

[0071] The chopped magnesium silicate fiber has a length of 150 μm and an aspect ratio of 1000.

[0072] The average particle size of the polymethyl methacrylate microspheres is 200 μm.

[0073] This embodiment also provides a method for preparing the above-mentioned three-dimensional ceramic glaze, the steps of which are as follows: E12. Transparent base frit, zircon sand, aluminum titanate and cerium oxide are mixed and ball-milled until the product particle size D90 < 10 μm. Short-cut magnesium silicate fiber, polymethyl methacrylate microspheres and suspending agent are added and stirred and mixed (dry mixing). Water is then added and mixed and aged.

[0074] The stirring speed for mixing was 80 rpm and the time was 5 min. The aging time is 24 hours.

[0075] Comparative Example 1 Comparative Example 1 provides a ceramic three-dimensional glaze, which is composed of the following components in parts by weight: 65 parts transparent base frit, 10 parts zircon sand, 8 parts aluminum titanate, 4 parts polymethyl methacrylate microspheres, 0.6 parts carboxymethyl cellulose, and 50 parts water.

[0076] The transparent base frit is composed of the following components by mass fraction: 63% SiO2, 12% Al2O3, 5% CaO, 6% MgO, 3% ZnO, 11%B2O3.

[0077] The chopped magnesium silicate fiber has a length of 100 μm and an aspect ratio of 800.

[0078] The average particle size of the polymethyl methacrylate microspheres is 100 μm.

[0079] This comparative example also provides a method for preparing the above-mentioned ceramic three-dimensional glaze, with the same steps as in Example 1.

[0080] Comparative Example 2 Comparative Example 2 provides a ceramic three-dimensional glaze, which is composed of the following components in parts by weight: 65 parts transparent base frit, 10 parts zircon sand, 8 parts aluminum titanate, 5 parts magnesium silicate fiber, 4 parts polymethyl methacrylate microspheres, 0.6 parts carboxymethyl cellulose, and 50 parts water.

[0081] The transparent base frit is composed of the following components by mass fraction: 63% SiO2, 12% Al2O3, 5% CaO, 6% MgO, 3% ZnO, 11%B2O3.

[0082] The magnesium silicate fiber has a length of 300 μm and an aspect ratio of 2000.

[0083] The average particle size of the polymethyl methacrylate microspheres is 100 μm.

[0084] This comparative example also provides a method for preparing the above-mentioned ceramic three-dimensional glaze, with the same steps as in Example 1.

[0085] To verify the advancement of the ceramic three-dimensional glaze and its preparation method provided in this embodiment of the invention, the ceramic three-dimensional glazes provided in this embodiment and the comparative example were applied to bisque-fired blanks and fired. The height of the glaze surface protrusion after firing is shown in Table 1 below. The wear resistance of the glaze surface was then tested, and the mass loss is shown in Table 1 below. Taking Example 1 as an example, the appearance of the fired glaze surface is as follows... Figure 1 As shown.

[0086] The steps of applying the coating to the bisque and firing it are as follows: (1) The viscosity of the ceramic three-dimensional glaze provided in the embodiments or comparative examples of the present invention is adjusted to 62000 mPa·s ± 1000 mPa·s by adding water.

[0087] (2) Apply a thick coat of wool to the bisque-fired blank with a brush, with a thickness of about 1.8 mm ± 0.2 mm.

[0088] (3) Dry naturally at room temperature for 24 hours, then dry in an oven at 60℃ for 2 hours.

[0089] (4) Firing: Heat the glazed bisque at a heating rate of 3℃ / min, hold at 900℃ for 30min, then raise to 1200℃ and hold for 20min, and then cool naturally.

[0090] Table 1

[0091] From the table above and the accompanying drawings in the instruction manual, at least the following conclusions can be drawn: (1) In Comparative Example 1, the raw materials for preparing the ceramic three-dimensional glaze do not contain cerium oxide and short-cut magnesium silicate fibers. The height of the glaze surface after firing is much lower than that in the Example, and the wear is large. In contrast, the raw materials for preparing the ceramic three-dimensional glaze in Comparative Example 2 do not contain cerium oxide, and the magnesium silicate fibers are long fibers. Although the height of the glaze surface is higher than that in Comparative Example 1, it is still lower than that in the Example; the wear is large. It can be seen that in the ceramic three-dimensional glaze provided by the present invention, the transparent base frit is used to form a continuous glass matrix; zircon sand decomposes at high temperature to produce ZrO2 and SiO2, inducing micro-expansion of volume; aluminum titanate has a high coefficient of thermal expansion, and the expansion mismatch with the matrix generates compressive stress, which promotes local bulging of the glaze surface; cerium oxide is used as a whisker growth promoter (cerium silicate whiskers); short-cut magnesium silicate fibers partially melt at high temperature and guide the whisker orientation growth to form a skeleton to support the protrusions; polymethyl methacrylate microspheres maintain the stability of the glaze during firing and prevent the precipitation of cerium oxide, short-cut magnesium silicate fibers, etc., which would lead to glaze surface collapse and uneven defects.

[0092] (2) Figure 1 In the sample, the glaze surface shows obvious protrusions, is smooth, and has a uniform color. Therefore, it is evident that the ceramic three-dimensional glaze provided in this embodiment of the invention exhibits minimal collapse after firing and can maintain its three-dimensional state to a high degree.

[0093] It should be noted that the present invention is not limited to the above-described embodiments. The above embodiments are merely examples, and any embodiments that have the same structure and perform the same effects as the technical concept within the scope of the present invention are included within the scope of the present invention. Furthermore, various modifications that can be conceived by those skilled in the art to the embodiments, and other ways of constructing by combining some of the constituent elements of the embodiments, without departing from the spirit of the present invention, are also included within the scope of the present invention.

Claims

1. A three-dimensional ceramic glaze, characterized in that, The components include the following parts by weight: 60-70 parts transparent base frit, 8-12 parts zircon sand, 5-10 parts aluminum titanate, 5-10 parts cerium oxide, 3-7 parts chopped magnesium silicate fiber, 3-5 parts polymethyl methacrylate microspheres, 0.5-0.8 parts suspending agent, 45-50 parts water.

2. The ceramic three-dimensional glaze according to claim 1, characterized in that, The transparent base frit comprises the following components by mass fraction: 59%~66% SiO2, 10%~15% Al2O3, 3%~6% CaO, 4%~8% MgO, 1%~5% ZnO, 5%~16% flux.

3. The ceramic three-dimensional glaze according to claim 2, characterized in that, The flux includes B2O3.

4. The ceramic three-dimensional glaze according to claim 3, characterized in that, The flux also includes alkali metal oxides.

5. The ceramic three-dimensional glaze according to claim 4, characterized in that, The alkali metal oxide includes at least one of K2O, Na2O, and Li2O.

6. The ceramic three-dimensional glaze according to any one of claims 1 to 5, characterized in that, It satisfies at least one of the following characteristics (1) to (6): (1) The particle size D50 of the zircon sand is ≤1.5μm; (2) The particle size D50 of the aluminum titanate is 3μm~5μm; (3) The particle size D50 of the cerium oxide is 50nm~100nm; (4) The length of the chopped magnesium silicate fiber is 50 μm to 150 μm; (5) The aspect ratio of the chopped magnesium silicate fiber is 500~1000; (6) The suspending agent includes carboxymethyl cellulose.

7. A method for preparing a ceramic three-dimensional glaze as described in any one of claims 1 to 6, characterized in that, Includes the following steps: After ball milling transparent base frit, zircon sand, aluminum titanate and cerium oxide, short-cut magnesium silicate fiber, polymethyl methacrylate microspheres and suspending agent are added and stirred and mixed. Water is then added and the mixture is aged.

8. The method for preparing ceramic three-dimensional glaze according to claim 7, characterized in that, The particle size D90 of the product obtained by the mixed ball milling is <10 μm.

9. The method for preparing ceramic three-dimensional glaze according to claim 7 or 8, characterized in that, It satisfies at least one of the following characteristics (1) to (3): (1) The stirring speed for the mixing process is 50 rpm to 80 rpm; (2) The mixing time is 3 min to 5 min; (3) The aging time is 24h~26h.

10. The application of a ceramic three-dimensional glaze as described in any one of claims 1 to 6 in ceramic glazing processes.